Patterns of neurobehavioral functioning in school-aged survivors of neonatal jaundice and hypoxic-ischemic encephalopathy in Kilifi, Kenya: A cross-sectional study [version 2; peer review: 1 approved with reservations, 2 not approved] - Magai, D; Newton, C; Mwangi, P; Koot, H; Abubakar, A (F1000Research, 2019)
Background: Studies in high-income countries have reported that school-aged children who survive neonatal jaundice (NNJ) and hypoxic-ischemic encephalopathy (HIE) develop long-term neurocognitive problems. However, less is known about the patterns of functioning in school-aged survivors of NNJ and HIE in sub-Saharan Africa. This study examined patterns of functioning in school-aged children who survived NNJ and HIE in Kilifi, Kenya.